2022
DOI: 10.1038/s42004-022-00749-6
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular charge-transfer enhances energy transfer efficiency in carotenoid-reconstituted light-harvesting 1 complex of purple photosynthetic bacteria

Abstract: In bacterial photosynthesis, the excitation energy transfer (EET) from carotenoids to bacteriochlorophyll a has a significant impact on the overall efficiency of the primary photosynthetic process. This efficiency can be enhanced when the involved carotenoid has intramolecular charge-transfer (ICT) character, as found in light-harvesting systems of marine alga and diatoms. Here, we provide insights into the significance of ICT excited states following the incorporation of a higher plant carotenoid, β-apo-8′-ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…31−35 Furthermore, a proper description of charge transfer states is desirable, since it was recently shown that intramolecular charge transfer (CT) states greatly speed-up the energy transfer to bacteriochlorophyll a. 36 In this work, we set out for remedying the weaknesses of the previous DFT/MRCI Hamiltonians with regard to double excitations while retaining the good performance for CT, Rydberg, and singly excited states known from the previous formulations. 37 −39 We will present a novel ansatz, which differentiates between double excitations involving the same spatial orbital twice and double excitations involving different spatial orbitals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31−35 Furthermore, a proper description of charge transfer states is desirable, since it was recently shown that intramolecular charge transfer (CT) states greatly speed-up the energy transfer to bacteriochlorophyll a. 36 In this work, we set out for remedying the weaknesses of the previous DFT/MRCI Hamiltonians with regard to double excitations while retaining the good performance for CT, Rydberg, and singly excited states known from the previous formulations. 37 −39 We will present a novel ansatz, which differentiates between double excitations involving the same spatial orbital twice and double excitations involving different spatial orbitals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To accomplish a proper modeling of SF and TTA-UC by quantum chemical methods, a balanced description of singly and doubly excited states is mandatory. Doubly excited states also play a pivotal role for the light-harvesting and protective functions of carotenoids in photosynthetic complexes. , In these compounds, the S 1 state is characterized by a mixture of the two singly excited π H–1 → π L and π H → π L+1 configurations and the doubly excited π H 2 → π L 2 configuration, while the optically bright S 2 state originates mainly from the π H → π L excitation. , The importance of double excitations is known to increase with growing conjugation lengths N . Experimental results strongly suggest that in carotenoids with N ≥ 11, an additional doubly excited dark state is located between S 2 and S 1 , which speeds up the deactivation of the S 2 state. Furthermore, a proper description of charge transfer states is desirable, since it was recently shown that intramolecular charge transfer (CT) states greatly speed-up the energy transfer to bacteriochlorophyll a …”
Section: Introductionmentioning
confidence: 99%
“…Patalag et al revealed the limitations of FRET theory and fastest excitation energy transfer (∼39 fs) in ethylene-bridged BODIPY heterooligomers using global analysis of femtosecond transient absorption spectra and mixed quantum-classical dynamic simulations . Using the global and target analyses, Yukihira et al reported that the intramolecular charge-transfer excited state of β-apo-8′-carotenal enhanced the energy transfer efficiency in carotenoid-reconstituted light-harvesting 1 (LH1) complex …”
Section: Introductionmentioning
confidence: 99%
“…26 Using the global and target analyses, Yukihira et al reported that the intramolecular charge-transfer excited state of β-apo-8′-carotenal enhanced the energy transfer efficiency in carotenoid-reconstituted light-harvesting 1 (LH1) complex. 27 Here, to understand the intermolecular resonance energy transfer dynamics of OLED materials of PVK and OXD, their ultrafast excited-state relaxation pathways are investigated in solution (tetrahydrofuran (THF)) and film states using femtosecond pump−probe spectroscopy, nanosecond laser flash photolysis, and time-correlated single photon counting spectrometer (TCSPC). It is found that there is an occurrence of efficient FRET (∼90%) from PVK to OXD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms behind their high efficiency in this energy transfer process are still debated [4][5][6][7][8][9][10][11]. A detailed understanding of the excited-state dynamics of carbonyl-containing carotenoids will be important for developing highly efficient, energy transfer systems for artificial photosynthesis [12,13].…”
Section: Introductionmentioning
confidence: 99%